Cybercrime and espionage : an analysis of subversive multivector threats - Gragido, Will.; Pirc, John.; Rogers, Russ. (Rockland, Mass. : Elsevier Science, 2011)
Cybercrime and Espionage provides a wealth of knowledge related to the realities seen in the execution of advanced attacks, their success from the perspective of exploitation and their presence within all industry. This book will educate you on realities of advanced, next generation threats, which take form in a variety ways. The authors, working in conjunction with strategic technology partners have key insights into the realm of what these new threats, dubbed'Subversive Multi-Vector Threats' or'SMT's. Whether the goal is to acquire and subsequently sell intellectual property from one organization to a competitor or the international black markets, to compromise financial data and systems, or undermine the security posture of a nation state by another nation state or sub-national entity, these threats are real and growing at an alarming pace. Includes detailed analysis and examples of the threats in addition to related anecdotal information. Author's combined backgrounds of security, military, and intelligence, give you distinct and timely insights. Presents never before published information: identification and analysis of cybercrime and the psychological profiles that accompany them.
Cybercrime and espionage and the new security 101 -- Evolution revolution -- The silent killer : how regulatory compliance has worsened the state of information security -- Mediating the great divorce : the convergence of physical and logical security -- Nonstate sponsored attacks : stealing information is our business, and business is good -- State-sponsored intelligence -- Cyber X : criminal syndicates, nation states, subnational entities, and beyond -- The rise of the subversive multivector threats -- Seven commonalities of subversive multivector threats -- Examples of compromise and presence of subversive multivector threats -- Hiding in plain sight : next-generation techniques and tools for avoidance and obfuscation -- Weapons of our warfare : next-generation techniques and tools for detection, identification, and analysis.
Includes bibliographical references and index.
Keywords: Computer crimes; Espionage; Security systems; Computer crimes -- Prevention; Business intelligence; Threats -- Safety measures